Hotspot geopolitics versus geosocial solidarity: Contending constructions of safe space for migrants in Europe. (December 2020) - Mitchell, Katharyne; Sparke, Matthew
This article examines how contending constructions of safe space for migrants reflect the geopoliticization of humanitarianism and its geosocial discontents. It contrasts geopolitical constructions of safe space that have been used by European authorities to justify and administer Hotspots with geosocial efforts to construct safe space through practices of solidaristic accommodation. The article documents the ways in which Hotspots have made migrants unsafe, even as they have been simultaneously justified in humanitarian terms as making both Europe and refugees safer. It further illustrates, by contrast, how counter-constructions of safe space can take divergent geosocial forms. These varied geosocial formations of accommodation emerge out of embodied space-making struggles for physical safety, personal dignity, organizational autonomy, radical democracy, spatial liberty, and social community. They create context-contingent alternatives to Hotspot geopolitics as well as opportunities for migrants and their allies to critique the limits of official humanitarianism. But they also remain overdetermined by the dominant border politics that Hotpots are supposed to secure. For these reasons, the borderlands between the abstract geopolitics of Hotspot humanitarianism and the embodied geosocial constructions of solidarity show safe space to be at once complex, compromised, and constantly contested.